(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Autoclaving-cooling is a starch physical modification technique widely used to analyze the increase in resistant starch levels in foodstuffs. However, this technique has a different effect on each high-carbohydrate diet. This study investigates the type of carbohydrate food to increase the levels of resistant starch through the autoclaving-cooling process. This study used 31 articles using the PRISMA method. Data were analyzed with Effect Size Hedges'd (standardized mean difference/SMD) and confidence interval (CI) using OpenMEE software. The results showed that the autoclaving-cooling method had a significant effect on increasing levels of resistant starch and prebiotic properties (SMD 6.633; 95% CI: 5.286 to 7.980; p<0.001). In conclusion, this study confirmed that the autoclaving-cooling method had a significant effect with a 95% confidence level in increasing the levels of resistant starch and prebiotic properties of high-carbohydrate foods.